Combinations of LiPO2F2 and Other Electrolyte Additives in Li[Ni0.5Mn0.3Co0.2]O2/Graphite Pouch Cells. Issue 9 (1st January 2018) - Ma, Lin; Ellis, Leah; Glazier, S. L.; Ma, Xiaowei; Dahn, J. R.
Abstract : Lithium difluorophosphate (LiPO2 F2 ) is a useful electrolyte additive for Li-ion cells. In this study, combinations of several selected additives and LiPO2 F2 were explored in Li[Ni0.5 Mn0.3 Co0.2 ]O2 (NMC532)/graphite pouch cells using high temperature storage testing (60°C), ultra-high precision coulometry (UHPC), electrochemical impedance spectroscopy (EIS), isothermal microcalorimetry and long term charge-discharge cycling. Several useful additives to use in combination with LiPO2 F2, were found, especially vinylene carbonate (VC), difluoroethylene carbonate (DiFEC) and fluoroethylene carbonate (FEC). These electrolyte additive combinations (e.g. LiPO2 F2 + FEC, LiPO2 F2 + VC, LiPO2 F2 + DiFEC) are effective in NMC532/graphite pouch cells since they were found to improve coulombic efficiency, extend charge-discharge cycle lifetime, decrease parasitic heat flow and control impedance growth. The compositions of the solid electrolyte interphases (SEI) on both positive and negative electrodes were enhanced in fluorine and phosphorous when LiPO2 F2 was used and the fluorine content was further enhanced when FEC or VC were included along with LiPO2 F2 . The oxygen content of the negative electrode SEI diminished when LiPO2 F2 was used and further reduced when FEC or VC were included. These changes to the SEI layers may explain why the combination of LiPO2 F2 with other additives can improve the lifetime and performance of Li-ion cells.